Exposure to Particles and Nitrogen Dioxide Among Workers in the Stockholm Underground Train System - N. Plato; C. Bigert; B.-M. Larsson; M. Alderling; M. Svartengren; P. Gustavsson (Elsevier, 2019)
Objectives: Exposure to fine particles in urban air has been associated with a number of negative health effects. High levels of fine particles have been detected at underground stations in big cities. We investigated the exposure conditions in four occupational groups in the Stockholm underground train system to identify high-exposed groups and study variations in exposure. Methods: PM1 and PM2.5 were measured during three full work shifts on 44 underground workers. Fluctuations in exposure were monitored by a real-time particle monitoring instrument, pDR, DataRAM. Qualitative analysis of particle content was performed using inductively coupled plasma mass spectrometry. Nitrogen dioxide was measured using passive monitors. Results: For all underground workers, the geometric mean (GM) of PM1 was 18 μg/m3 and of PM2.5 was 37 μg/m3. The particle exposure was highest for cleaners/platform workers, and the GM of PM1 was 31.6 μg/m3 [geometric standard deviation (GSD), 1.6] and of PM2.5 was 76.5 μg/m3 (GSD, 1.3); the particle exposure was lowest for ticket sellers, and the GM of PM1  was 4.9 μg/m3 (GSD, 2.1) and of PM2.5 was 9.3 μg/m3 (GSD, 1.5). The PM1 and PM2.5 levels were five times higher in the underground system than at the street level, and the particles in the underground had high iron content. The train driver's nitrogen dioxide exposure level was 64.1 μg/m3 (GSD, 1.5). Conclusions: Cleaners and other platform workers were statistically significantly more exposed to particles than train drivers or ticket sellers. Particle concentrations (PM2.5) in the Stockholm underground system were within the same range as in the New York underground system but were much lower than in several older underground systems around the world. Keywords: Airborne exposure, Occupation, Particle exposure, Subway